U.S. inspectors general : truth tellers in turbulent times - Johnson, Charles A., 1948-; Newcomer, Kathryn E., 1949- (Brookings Institution Press, 2020)
"Inspectors general are important players in the federal government, and their work often draws considerable public attention when one of them uncovers serious misdeeds or mismanagement that make the headlines. This book by two experts in public policy provides a comprehensive, up-to-date examination of how inspectors general have operated in the four decades since Congress established the offices to investigate waste, fraud, and mismanagement at federal agencies and to promote efficiency and effectiveness in government programs. Unique among federal officials, inspectors general are independent of the agencies they monitor, and they report to the executive and legislative branches of government. One key factor in their independence is that they are expected to be non-partisan and carry out their work without regard to partisan interests. The authors of U.S. Inspectors General: Truth Tellers in Turbulent Times emphasize the "strategic environment" in which inspectors general work and interact with a variety of stakeholders, inside and outside the government. Their new book is based on in-depth case studies, a survey of inspectors general, and a review of public documents related to the work of inspectors general. It will be of interest to scholars and students of public policy and public management, journalists, and ordinary citizens interested in how the government works, or doesn't work, on their behalf"--Publisher's description.